Cat preantral follicle survival after prolonged cooled storage followed by vitrification - Martins, Jorge Luis Araújo [UNESP]; Lopes, Maria Denise [UNESP]; de Souza, Fabiana Ferreira [UNESP]; Possebon, Fabio Sossai [UNESP]; Wibbelt, Gudrun; Jewgenow, Katarina (Elsevier, 2018)
The aim of this study was to investigate the impact of prolonged storage at 4 °C on survival of cat preantral follicles (PAFs) pre- and post-vitrification. Ovaries were obtained from 12 queens and transported at 4 ºC within 2–6 h. Parts of the ovaries were stored for an additional 24 h or 72 h. The ovarian cortex was dissected, analyzed for viability (neutral red - NR) and morphology (histology - HE and ultrastructural analysis by TEM) and vitrified. We used 2 mm biopsy punches to obtain equal size pieces as the experimental units. After NR assessment, each sample was fixed and embedded in paraffin for HE staining to determine the number of morphologically intact follicles. Another 2 mm piece of ovary was subjected to TEM. NR viability assessment and HE results showed a similar tendency with PAF survival postvitrification even after prolonged cooling at 24 h and 72 h. With TEM, integrity of mitochondria, plasma and basal membranes as well as the presence of pre-granulose cells of PAFs were documented postvitrification for the control group and 24 h prolonged storage group, but not after 72 h storage. Our results showed that cat PAFs can survive prolonged storage followed by vitrification. The described set of techniques are applicable towards creating a gamete bank for endangered feline species.